Robotic Process Automation: Hype or Hope? - Hindel, Julia; Cabrera Pérez, Lena; Stierle, Matthias (Proceedings of the 15th International Conference on Wirtschaftsinformatik, 2020)
Robotic Process Automation (RPA) is a fast-emerging process automation technology suited for high-volume, repetitive, and rule-based tasks. The promises of rising RPA vendors and the lack of documented track records leave researchers and practitioners with the challenge of positioning the term and assessing RPA’s true potential. To objectively discuss the strengths and weaknesses of this technology, we conduct a literature review, a practical implementation of an RPA solution, and an interview with an industry expert. We reveal that the current literature primarily focuses on economic factors. This paper, therefore, adds various social and technical aspects to the discussion. Most importantly, robustness and stability pose technical challenges for successfully implementing RPA. Further research directed at error handling and maintenance of software robots is required to support the successful implementation of RPA.<br
Keywords: Robotic Process Automation; Software Robotics; Business Process Management; Automation